PSYCHOLOGICAL VIEWS AND SOLUTIONS IN THE PHILOSOPHY OF LITERATURE - Doston Khamidov (American Journals Publishing, 2024)
In this article, it is noted that a relatively new direction in our literary criticism is the essence of the philosophy of literature as a product of world-class scientific and literary interpretation. Analysis of selected works of both classic and modern new literature. Also, the philosophy of literature is a set of high and great global meanings that are covered and seen with the eyes of the heart and the eyes of the pure mind.
Keywords: Global interpretation, philosophy, image, plot, art, word, classic novel.